2012
DOI: 10.3945/an.112.002758
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Imbalance: a Pathological Metabolic Marker

Abstract: Perturbations in methyl group metabolism and homocysteine balance have emerged over the past few decades as having defining roles in a number of pathological conditions. Numerous nutritional, hormonal, and genetic factors that are characterized by elevations in circulating homocysteine concentrations are also associated with specific pathological conditions, including cancer development, autoimmune diseases, vascular dysfunction, and neurodegenerative disease. Although much remains to be explored, our understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 98 publications
3
115
1
2
Order By: Relevance
“…Trans-sulfuration is favored with the upregulation of CBS. Several studies have reported that increased trans-sulfuration resulted in higher levels of cysteine, which can serve as a substrate for gluconeogenesis via its conversion to pyruvate, leading to hyperglycemia (14,29,37). However, we observed that random glucose levels were lower in the DJB group than in the control group.…”
Section: Discussioncontrasting
confidence: 54%
“…Trans-sulfuration is favored with the upregulation of CBS. Several studies have reported that increased trans-sulfuration resulted in higher levels of cysteine, which can serve as a substrate for gluconeogenesis via its conversion to pyruvate, leading to hyperglycemia (14,29,37). However, we observed that random glucose levels were lower in the DJB group than in the control group.…”
Section: Discussioncontrasting
confidence: 54%
“…Finally, we did not analyze different types of alcoholic beverages. Inconsistent findings may exist because the effect of alcohol depends on the type of alcoholic beverage, as beer is a rich source of folate and vitamin B 6 , whereas red wine and spirits contain negligible amounts of these vitamins. 47 In conclusion, the present study demonstrates a strong interaction between the MTHFR 677TT genotype and lifestyle variables and an increase in the risk of elevated blood Hcy concentrations in young adult males.…”
Section: Discussionmentioning
confidence: 99%
“…Hcy acts as a key intermediate in one-carbon metabolism being metabolized through two vitamin B-dependent pathways, which are controlled by three key enzymes-methylenetetrahydrofolate reductase (MTHFR), methionine synthase and cystathionine beta-synthase 1 A high blood concentration of Hcy has been recognized as an independent risk factor for cardiovascular diseases in observational studies, [2][3][4] and is also associated with several other disorders such as neural tube defects and non-syndromic oral clefts. 5,6 Although the benefits from homocysteine lowering interventions for cardiovascular diseases have not been confirmed, 7 it is plausible that the positive effect is exclusively related to stroke risk. 8 The inconsistency related to hyperhomocysteinemia as a cause of cardiovascular diseases could result from the interactions between nutrients, metabolic and genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Considering plasma homocystine concentrations are highly dependent on intracellular homocysteine metabolism in liver (Schalinske and Smazal, 2012), and cystathionine is a sensitive marker of changes in flux through the transsulfuration pathway (Guttormsen et al, 2004), the greater homocystine and cystathionine indicate increased hepatic flux through this pathway in response to MET supplementation. In addition to the involvement of sulfur-containing compounds, the fact that circulating concentrations of α-aminobutyric acid also was greater in MET-supplemented cows indicates increased flux through the transsulfuration pathway (Stabler et al, 2009) Around parturition, the increased demand for nutrients and energy leads to an increase in the production reactive oxygen metabolites (ROM), the accumulation of which could deplete antioxidants and give rise to oxidative stress that may cause substantial tissue damage and render cows more susceptible to various health disorders (Bernabucci et al, 2005, Castillo et al, 2005.…”
Section: Sulfur-containing Compound Pool and Metabolismmentioning
confidence: 99%